Soft-tissue outcomes following implantation of different types of bone conduction hearing devices in a single centre. Issue 12 (29th December 2019) - Ray, J; Lau, K; Moraleda, J; Yardley, M; Dawoud, M; Dimitriadis, P A
Abstract: Objective: To compare soft-tissue complications following implantation of different bone conduction hearing devices. Methods: Adults who underwent implantation of different bone conduction hearing devices, between January 2008 and December 2016, were included in the study. Five groups were identified depending on the soft-tissue approach: (1) split-thickness skin flap with use of dermatome; (2) Sheffield 'S'-shaped incision with skin thinning; (3) linear incision without skin thinning (hydroxyapatite-coated abutment); (4) 'C'-shaped full-thickness incision for passive transcutaneous bone conduction hearing devices; and (5) post-aural incision for active transcutaneous bone conduction hearing devices. The main outcome measures were different soft-tissue complications. Results: The study comprised 120 patients (group 1 = 20 patients, group 2 = 35, group 3 = 35, group 4 = 20, and group 5 = 10). Soft tissue related problems were encountered in 55 per cent of patients from group 1, 26 per cent in group 2, 3 per cent in group 3, and 0 per cent in groups 4 and 5. Conclusion: There was a reduction in soft tissue related complications with reduced soft-tissue handling. In addition, there was a shift from an initial skin-penetrating (percutaneous) approach to a non-skin-penetrating (transcutaneous) approach.